2005
DOI: 10.1007/s10940-004-1785-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity and Accuracy of Geographic Profiling Strategies

Abstract: Geographic profilers have access to a repertoire of strategies for predicting a serial offender's home location. These strategies range in complexity-some involve more calculations to implement than others-and the assumption often made is that more complex strategies will outperform simpler strategies. In the present study, we tested the relationship between the complexity and accuracy of 11 strategies. Data were crime site and home locations of 16 UK residential burglars who had committed 10 or more crimes ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
3
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 29 publications
10
114
3
9
Order By: Relevance
“…Geographic profiling involves predicting the home location of an at-large serial offender based on information about where that offender has committed his or her crimes (Canter & Larkin, 1993;Rossmo, 1993;Snook, Canter, & Bennell, 2002;Snook, Taylor, & Bennell, 2004;Snook, Zito, Bennell, & Taylor, 2005). In order to determine if geographic profiling will succeed or fail for a particular type of serial crime in a particular environment, it should be demonstrated that the assumptions upon which the geographic profiling technique is based correspond with what is known about the spatial decisions of serial offenders in that environment.…”
mentioning
confidence: 99%
“…Geographic profiling involves predicting the home location of an at-large serial offender based on information about where that offender has committed his or her crimes (Canter & Larkin, 1993;Rossmo, 1993;Snook, Canter, & Bennell, 2002;Snook, Taylor, & Bennell, 2004;Snook, Zito, Bennell, & Taylor, 2005). In order to determine if geographic profiling will succeed or fail for a particular type of serial crime in a particular environment, it should be demonstrated that the assumptions upon which the geographic profiling technique is based correspond with what is known about the spatial decisions of serial offenders in that environment.…”
mentioning
confidence: 99%
“…Furthermore, centrographic methods are often presented as diagnostic routines that provide benchmarks for assessing the performance of multiple methods Paulsen, 2006a;Levine, 2009). However, single descriptive measures such as these are susceptible to outliers, and are thus often criticized for their inability to provide an efficient search strategy for locating an anchor point (Levine, 2005;Snook et al, 2005;Taylor, Bennell, & Snook, 2009). …”
Section: Contemporary Geographic Profiling Modelsmentioning
confidence: 99%
“…Despite the popularity, JTC estimation models are often criticized for theoretical and empirical limitations (van Koppen & de Keijser, 1997;Rengert et al, 1999;Snook et al, 2005;Smith, Bond, & Townsley, 2009). To overcome these caveats, many researchers have pursued, with notable success, alternative heuristics for profiling offender behavior in space (Paulsen, 2006a;Snook, Canter, & Bennell, 2002;Snook et al, 2005;Taylor, Bennell & Snook, 2009). However, these techniques continue to omit the environmental factors associated with criminal opportunity and target attractiveness.…”
Section: Contemporary Geographic Profiling Modelsmentioning
confidence: 99%
See 2 more Smart Citations